INFLUENCE OF SPACE WEATHER EFFECTS ON THE UPPER ATMOSPHERE ACCORDING TO THE DRAG OF ARTIFICIAL EARTH SATELLITES - Komendant, V. H.; Koshkin, N. I.; Ryabov, M. I.; Sukharev, A. L. (Одеські астрономічні публікації, 2014)
The applying of the method of timefrequency analysis allows to reveal the detailed structure of the manifestations of the influence of the space weather's state on the upper atmosphere of the Earth. The sensitive indicator of such changes are low-orbit satellites. The drag dynamics of five low–orbit satellites was viewed as indicators manifestations of the influence of space weather on the Earth upper atmosphere. The study period includes phases of decay and a long minimum of 23-rd solar cycle, phases of growth and maximum of 24-th solar cycle. In drag dynamics of all the analyzed satellites strongly marked regular drag effects with long periods (2-4 years) and short-period effects with periods less than one year. The satellites with orbital inclinations close to the equator shows periods with trend from 25 days to 1,3 months.